Strengthening capacity to use research evidence in health sector policy-making: experience from Kenya and Malawi - Rose N. Oronje; Violet I. Murunga; Eliya M. Zulu (BMC, 2019)
Abstract Background Among the many barriers to evidence use in decision-making, weak capacity for evidence use has attracted a lot of focus in the last decade. The study aims to inform and enrich ongoing and future efforts to strengthen capacity for evidence use by presenting and discussing the experiences and lessons of a project implemented in Kenya and Malawi to strengthen individual and institutional capacity for evidence use within the ministries of health (MoHs). Methods This paper draws on the internal and external evaluations of a 3-year project funded by the United Kingdom's Department for International Development, the Strengthening Capacity to Use Research Evidence in Health Policy (SECURE Health). To strengthen individual capacity, the project implemented a training and mentorship programme for 60 mid-level policy-makers in the two MoHs. To strengthen institutional capacity, the project conducted sustained advocacy with top leaders to strengthen structures that enable evidence-informed decision-making (EIDM), supported Kenya to develop research-for-health policies and priorities, supported Malawi to review the implementation of its health research agenda, developed EIDM guidelines for both MoHs, and supported bi-annual evidence dialogues to improve interactions and raise the profile of evidence. Internal evaluation included baseline and endline surveys (93 baseline and 92 endline interviews), 60 in-depth interviews, and intervention-specific evaluations (pre-post tests for training workshops, feedback forms for policy dialogues and tracking effects of advocacy efforts). The external evaluation was implemented alongside project implementation, conducting three annual evaluations. Results The results show that training and mentorship programmes in EIDM were effective in improving competencies of civil servants. However, such programmes need to train a critical mass to be effective in enhancing EIDM practice at the MoHs. On strengthening institutional capacity for EIDM, while the project achieved some success, it did not realise long-lasting effects because of its limited time of implementation and limited focus on sustained political economy analysis, which meant that the intervention was negatively affected by frequently changing interests within the MoHs. Conclusions Although training and mentorship are effective in improving EIDM competencies, they need to be incorporated in existing pre-service and in-service training programmes for sustainability. Strengthening institutional capacity for evidence use is complex and needs sustained political commitment and long-term investments.